Blendas de quitosana/poli (álcool vinílico) contendo emulsão de óleo de copaíba e nanopartículas de prata para possível aplicação em tratamento de feridas - MATOS, Taiana de Sousa (2022)
The investigation of new pharmaceutical forms for the treatment of wounds represents an important technological advance in the field of tissue engineering. In this context, films based on poly (vinyl alcohol) (PVA)/chitosan (CS) with copaiba oil emulsion and silver nanoparticles emerge as promising for use as dressings, seeking through a synergistic effect to obtain biomaterials with broad spectrums of biological action with the possibility of accelerating the repair and healing of injured tissues, such as wounds. Therefore, the present research had as objective the production and characterization of PVA/CS films in the proportions 0.2:0.8 (m/v), respectively, with 0.1% and 0.5% (v/v) of copaiba oil and 10 ml of silver nanoparticles by the casting method, aiming at its possible application in wounds. The silver nanoparticle and copaiba oil emulsion were analyzed by the UV/Vis technique (UV-Visible). The films were qualitatively evaluated by visual inspection, swelling, moisture and contact angle, as well as characterized by Fourier Transform Spectroscopy (FTIR). Overall, upon visual inspection, most films exhibited excellent optical transparency. As well as hydrophilic character and good degree of swelling in the presence of distilled water and PBS fluids, indicating that these films with copaiba oil and silver emulsion show promise for application as dressings in the regeneration of injured tissues. Therefore, through the evaluation of all results, BP 0.5% AGNPS (v/v) films may be more indicated for application when compared to the remaining samples.